2020
DOI: 10.3390/tropicalmed5020058
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions of Immigrant Parents Towards Human Papillomavirus (HPV) Vaccination: A Systematic Review

Abstract: Background: Our understanding about knowledge, attitudes and perceptions (KAP) of immigrants regarding human papillomavirus (HPV) vaccine is poor. We present the first systematic review on KAP of immigrant parents towards HPV vaccine offered to their children. Methods: Major bio-medical databases (Medline, Embase, Scopus and PsycINFO) were searched using a combination of keyword and database-specific terms. Following identification of studies, data were extracted, checked for accuracy, and synthesised. Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 51 publications
(123 reference statements)
2
39
4
Order By: Relevance
“…Importantly, although highlighted as a concern in the literature (33,34), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (33,34). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemicrelated information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, although highlighted as a concern in the literature (33,34), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (33,34). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemicrelated information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that rural residents were more likely to be hesitant toward vaccination is further consistent with findings showing more vaccine resistance among people residing in the suburbs than in cities (Murphy et al, 2021). Importantly, although highlighted as a concern in the literature (Alabdulla et al, 2021;Netfa et al, 2020), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (Alabdulla et al, 2021;Netfa et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, although highlighted as a concern in the literature (Alabdulla et al, 2021;Netfa et al, 2020), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (Alabdulla et al, 2021;Netfa et al, 2020). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemic-related information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence indicates low-income, minority, and immigrant groups are at increased risk of HPVassociated cancers [6][7][8][9]. Low or inadequate knowledge and awareness of HPV infection and the HPV vaccine have been linked to increased HPV-associate cancer risk among minorities [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%